Cost-effectiveness of a mindfulness-based mental health promotion program: economic evaluation of a nonrandomized controlled trial with propensity score matching - Müller, Gerhard; Bombana, Manuela; Schmahl, Christian; Bohus, Martin; Lyssenko, Lisa (BMC public health, 2019)
Mental health promotion programs have been shown to reduce the burden associated with mental distress and prevent the onset of mental disorders, but evidence of cost-effectiveness is scarce.